Synthesis, characterization of novel coupling products and 4-arylhydrazono-2-pyrazoline-5-ones as potential antimycobacterial agents - KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (My University, 2002)
Novel coupling products 7a-d and 4-arylhydrazono-2-pyrazoline-5-ones 8a-e were synthesized and evaluated for antimycobacterial activity against Mycobacterium tuberculosis H37Rv and Mycobacterium avium. Compound 7b was found to be the most potent derivatives of the 7a-d series by an MIC value of 6.25 microg/ml.
Keywords: Microbial Sensitivity Tests; Antitubercular Agents; Pyrazoles; Magnetic Resonance Spectroscopy; Mycobacterium tuberculosis; Mycobacterium avium